2015
DOI: 10.1039/c5lc00372e
|View full text |Cite
|
Sign up to set email alerts
|

Hot punching of high-aspect-ratio 3D polymeric microstructures for drug delivery

Abstract: COMMUNICATION This journal is © The Royal Society of Chemistry 2015Lab Chip, 2015, 00, 1-3 | 1 Oral drug delivery is the most preferable route of drug delivery. This is due to the ease of administration, flexibility in dosage and most importantly, patient compliance. 1 However, there are challenges with this route of delivery. These are non-specificity of the drug, degradation in the acidic environment of the stomach and low drug stability resulting in an overall low bioavailability of active ingredients.2,3 W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…Hot punching PLLA, PCL 29 Sealed microcontainers Spray coating Eudragit L100 11,12,18 Sealed microcontainers Thermal bonding PLGA, PC, PMMA 21,30 Microfabrication technologies and materials…”
Section: Microcontainersmentioning
confidence: 99%
See 2 more Smart Citations
“…Hot punching PLLA, PCL 29 Sealed microcontainers Spray coating Eudragit L100 11,12,18 Sealed microcontainers Thermal bonding PLGA, PC, PMMA 21,30 Microfabrication technologies and materials…”
Section: Microcontainersmentioning
confidence: 99%
“…However, the main drawback is that it is that is an epoxy based resin and potential accumulation in the GI tract could lead to unwanted side effects. Therefore, several methods for fabrication of drug delivery devices using biodegradable polymers have been proposed 26,27,29 . Tao et al have used soft lithography with SU-8 microstructures to prepare PDMS masters and subsequently performed microtransfer molding to define microwells in poly(lactic-glycolic acid) (PLGA) and gelatine ( Figure 2C) 26 .…”
Section: Microcontainersmentioning
confidence: 99%
See 1 more Smart Citation
“…Boisen and co-workers recently employed an inkjet printer to load a drug solution into microdevice reservoirs [121, 122], which is a quasi-no-waste performance technique as shown in Figure 4 B. They also loaded microdevice reservoirs with hydrophobic drugs in the absence of toxic organics by incorporating supercritical fluid impregnation with inkjet printing [123].…”
Section: Loading Of Novel Micro- and Nanoscale Oral Drug Delivery mentioning
confidence: 99%
“…Petersen et al reported hot punching as a modified hot embossing method of fabricating high aspect ratio 3D polymeric microstructures forming a reservoir with a volume in the nanoliter range for drug delivery [58]. An elastic PDMS layer was deposited between the poly-L-lactic acid (PLLA) layer and the hard Si substrate.…”
Section: Microreservoir-based Drug Delivery Systemsmentioning
confidence: 99%